(3dGejI GdYQH (B- (3bUjOIs - (3YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, CHh MaU, Rjf GdOjf GHf GdhQOj GdeYQj GdcfOj,J (B749 (3g` s
(3ChdgG (B:s
(3CbjehG Hfj oCej oUOhQ eWjoce aEfj Edi bhe ShGce dCejd s
(3BNQgG (B:s
(3hGdCYbd GdPj bO JYJUe HGdLHd jbGd hYd CYbd, hCQhjI oYbdGA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdNW ajg VHWs
(3fSNI KGfjIs
(3JNdh ef GdTQMs
(3hQO CjVkG JMJ Qbe (B2182(3, (B2185(3, (B2202 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B228 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B3s
Keywords: (3GdCOHs